Harder than it looks [compact disc] - Whibley, Deryck, 1980- (Simple Plan, 2022)
Simple Plan are back with their first new album since 2016's Taking One for the Team. Along with the single The Antidote, it includes a collaboration with Deryck Whibley of Sum 41.